The Effect of Single Co-expression of The DnaK-DnaJ-GrpE and GroEL/ES Chaperones and Their Combination on Expression Intein-pretrombin-2 in Escherichia coli ER2566 - Iman Permana Maksum; D Agus Yusuf Wildan; Khomaini Hasan; Toto Subroto (Jurnal Kimia Valensi, 2020)
The use of recombinant thrombin in the manufacture of fibrin glue allows diseases contamination to be avoided. However, the expression of recombinant protein in E. coli still has a disadvantage of the formation of inclusion bodies, so it needs to be minimized by co-expression of chaperones. Therefore, the aim of this study was to determine the effect of single DnaK-DnaJ-GrpE and GroEL/ES chaperone expression and their combination on the expression of intein-pretrombin-2Ti,pH on E. coli ER2566. The method started with isolation of pTWIN1-prethrombin-2Ti,pH and pG-KJE8 from E. coli TOP10F' and DH5α respectively, the co-transformation of the expression host E. coli ER2566 using pG-KJE8 and pTWIN1-prethrombin-2Ti,pHvectors, the chaperone co-expression was induced using L-Arabinosa before IPTG induction and cell culture growth was incubated at 22 oC. The expression products were characterized by using Sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis. The results of the co-expression of chaperone showed that the number of soluble fraction was higher than the one without co-expression of chaperone. In addition, the co-expression of chaperone using pG-KJE8 in intein-prothrombin-2Ti,pH expression was sufficient using tetracycline as an inducer.